2016
DOI: 10.1371/journal.pntd.0005194
|View full text |Cite
|
Sign up to set email alerts
|

Dengue in the Middle East and North Africa: A Systematic Review

Abstract: BackgroundDengue virus (DENV) infection is widespread and its disease burden has increased in past decades. However, little is known about the epidemiology of dengue in the Middle East and North Africa (MENA).Methodology / Principal FindingsFollowing Cochrane Collaboration guidelines and reporting our findings following PRISMA guidelines, we systematically reviewed available records across MENA describing dengue occurrence in humans (prevalence studies, incidence studies, and outbreak reports), occurrence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 99 publications
6
103
0
2
Order By: Relevance
“…The seroprevalence in this town was comparable to that in the South Indian state Tamil Nadu [25] and in several countries in Southeast Asia [24,26]. The seroprevalence was higher than in other countries in Africa and in the Middle East [3,27]. The seroprevalence data were also higher than what was previously reported from Sudan.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The seroprevalence in this town was comparable to that in the South Indian state Tamil Nadu [25] and in several countries in Southeast Asia [24,26]. The seroprevalence was higher than in other countries in Africa and in the Middle East [3,27]. The seroprevalence data were also higher than what was previously reported from Sudan.…”
Section: Discussionsupporting
confidence: 70%
“…The seroprevalence data were also higher than what was previously reported from Sudan. Previous studies from Port Sudan, Kassala, West Kordofan and the Northern Province found DENV IgG in 9–49% of the tested sera (reviewed in . Together the seroprevalence data indicate that further seroepidemiologic testing and surveillance are needed in Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies [2,3], there were an estimated 390 million annual cases of dengue fever and an estimated 3.9 billion people in 128 countries are at risk of being infected by dengue fever virus (DENV) with different serotypes. The DENV is affecting numerous areas in Eastern and Southeast Asia, such as China [4]; the lowlands of Nepal [5]; the slums in Delhi, India [6]; Hanoi, Vietnam [7]; and Iran [8] as well as other parts of the world, such as the Middle East, North Africa [9], and South America [10]. Due to the lack of effective treatment of severe dengue fever [11], accurate and early detection methods to identify the DENV serotype [5,12,13] are required in order to provide careful patient monitoring and to prevent the disease's progression to a more severe stage.…”
Section: Introductionmentioning
confidence: 99%
“…En estos inciden las actuaciones del equipo de atención de salud, y la debilidad en la calidad y oportunidad de la notificación epidemiológica (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionunclassified
“…Durante el 2016 se redujo a 2'427.290 casos en las Américas; el 67 % lo aportó Brasil, y el 11 % la Región Andina -donde está ubicada Colombia-, que registra el 35 % de los casos, y 8 % el istmo centroamericano (5,11). En Colombia, de acuerdo con el reporte de vigilancia epidemiológica, para la semana 23 de 2015 se registraron 46.538 casos de dengue (98,7 % correspondió a dengue y 1,3 % dengue grave), un incremento de 0,1 % con respecto al 2014.…”
Section: Introductionunclassified